1996
DOI: 10.1016/s0022-5223(96)70133-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for acquired heart disease looking for the artery of adamkiewicz: A quest to minimize paraplegia after operations for aneurysms of the descending thoracic and thoracoabdominal aorta

Abstract: All patients undergoing resection of thoracic or thoracoabdominal aneurysms at Mount Sinai Hospital since November 1993 had spinal cord function monitored with somatosensory-evoked potentials as part of a multimodality approach to reducing spinal cord injury. In the segment to be resected, each pair of intersegmental vessels was sequentially clamped, and they were subsequently sacrificed only if no change in somatosensory evoked potentials occurred within 8 to 10 minutes after occlusion. Adjunctive protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
162
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(171 citation statements)
references
References 10 publications
5
162
0
4
Order By: Relevance
“…However, the risk of operation is also unmanageable. The risk of spinal cord injury, particularly in operations on the descending aorta [9] , is also significant. As a result of surgical risk and expense, our patient elected for conservative treatment for his aneurysm 8 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of operation is also unmanageable. The risk of spinal cord injury, particularly in operations on the descending aorta [9] , is also significant. As a result of surgical risk and expense, our patient elected for conservative treatment for his aneurysm 8 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the segmental supply to the AKA, there are alternative routes by which the anterior spinal axis might be supplied. From our own experience 2 and that of others, 3 we know that spinal cord function is not always crucially dependent on segmental supply directly connecting to the AKA. Collaterals can substitute the spinal cord supply to maintain spinal cord function.…”
mentioning
confidence: 81%
“…Collaterals can substitute the spinal cord supply to maintain spinal cord function. 3 Recently, these collateral pathways have been visualized with MR angiography (MRA) 2 (Fig 1) and correlated with intraoperative spinal cord motor-evoked potentials. It is interesting to note in this study that when the segmental supply to the AKA was inside the cross-clamped aortic region and connecting collaterals originating from outside the cross-clamped aortic area were noticed, this had a predictive value of 97% for stable spinal cord function.…”
mentioning
confidence: 98%
“…They reported that quick oversewing of the intercostal arteries with CSF drainage and naloxone administration could help reduce the incidence of spinal cord injury. Griepp et al [80] also showed that reattachment could be avoided by ligating the intercostal arteries before aortic cross-clamping while monitoring somatosensory evoked potential. These reports suggest that existing collateral vessels might improve the perfusion pressure.…”
Section: Reattachment Of the Intercostal And Lumbar Arteriesmentioning
confidence: 99%